THE INTERDEPENDENCE, THE COOPERATION AND THE COORDINATION BETWEEN THE POLICE AND THE ARMY OF THE REPUBLIC OF MACEDONIA (Annual of the Faculty of Philosophy in Skopje, 2013)
This paper counterpoises a critical review for the need for coordination between the police and the Army of the Republic of Macedonia. The starting premise is that it has to be acted synchronal in order to enable space for canalizing the common activities and efforts in dealing with complex security situations. Jn that sense, a subject for critical debate today is the thesis for existence, or nonexistence of coordination of these two key subjects in the security system of the Republic of Macedonia, which are the base for achieving the peace and the security> in the country. From hence, the cogitation for the need of a higher degree of cooperation of all key subjects of the security system involved in the process of guaranteeing the peace and security in the country is imposed. The elaboration made for the cooperation and the coordination between the army and the police in the Republic of Macedonia in this paper is consisted from two elements: first, analysis are made of the coordination steps which are made by the police and the army in order to enable the needed cooperation and second, the analysis for the security? subjects, especially the police and the army is made in order to ascertain with what kind of problems they are facing in executing the common activities.
Keywords: COORDINATION; COOPERATION; COMMUNICATION; SECURITY SECTOR; POLICE; ARMY